Revival [compact disc, unabridged] : a novel - King, Stephen, 1947- (Simon & Schuster Audio, 2014)
A young boy, Jamie, and the new minister, Charles Jacobs share a deep bond based on a secret obsession. When tragedy strikes the Jacobs family, the preacher curses God and mocks all religious belief. Now an adult, Jamie has demons of his own. Addicted to heroin and desperate, Jamie meets Charles Jacobs again, with profound consequences for both men. Their bond becomes a pact beyond even the Devil's devising, and Jamie discovers that revival has many meanings.